Parámetros productivos de pollos parrilleros en pastoreo utilizando balanceado comercial - Intriago Zambrano, María Erlita (2023)
The purpose of the research was to evaluate the productive parameters of grazing broiler chickens using commercial balanced feed. 120 chickens were evaluated as an experimental unit, divided into 3 treatments in which the balanced feed level was considered (T1= 80%, T2 = 85% and T3 = 90%) with 4 repetitions. The variables studied were weekly body weight, weekly-accumulated feed intake, weekly feed conversion, carcass yield, mortality, viability and cost-benefit ratio. The distribution of the variables with respect to the treatments did not present a normal distribution during the experiment, therefore, the Kruskal Wallis test was applied. It was observed that treatment 3 presented the highest values for final body weight (2917 g). , daily weight gain (69.45 g) and feed conversion of 0.77, compared to the other T1 and T2 . In the same way, T3 obtained a higher percentage with respect to the yield of the carcass 84.49 and showed a benefit-cost ratio of 0.47 cents. No mortality was observed in any chicken in the treatments, indicating a viability rate of 100%. In conclusion, the supply of a diet that contains 90% balanced can significantly improve the productive parameters of grazing broiler chickens. In conclusion, the use of a diet that contains 90% balanced has shown to significantly improve the productive parameters in comparison with the use of diets with 80% and 85% balanced.